(untitled) (Journal of Libya for geographical studies, 2022)
This research deals with climatic classification in Derna region in north-east of Libya and the target of research is determine climatic variation using the "Bailey" classification, which depends on humidity coefficient (rain effectiveness) and heat effectiveness (heat extreme months), especially these two elements are most important climatic elements through which it is possible to identify the climate characteristics of any region in the world. The results of the moisture coefficient (rain efficiency) showed that the prevailing climate in the coastal and mountainous regions is semi-arid (D), and dry climate (E) in south areas where transitional zone between coast and desert, and effectiveness of rain gradually increases in to west areas, where the semi-humid climate in Green mountain region. The results of heat efficiency showed that prevailing climate in study area is warm climate represented by two climate (B1, B2) in most years, especially in coastal and mountainous regions and very warm which is represented by climate (A3) in some years. Based on evaluation of the research results, appropriate plans can be drawn up to identify the areas threatened by climatic drought in the southern edges of the study area.